Impact of a Breathing Intervention on Engagement of Abdominal, Thoracic, and Subclavian Musculature during Exercise, a Randomized Trial - Bahenský, Petr; Bunc, Václav; Malátová, Renata; Marko, David; Grosicki, Gregory J; Schuster, Jan (Journal of clinical medicine, 2021)
BACKGROUND: Breathing technique may influence endurance exercise performance by reducing overall breathing work and delaying respiratory muscle fatigue. We investigated whether a two-month yoga-based breathing intervention could affect breathing characteristics during exercise. METHODS: Forty-six endurance runners (age = 16.6 ± 1.2 years) were randomized to either a breathing intervention or control group. The contribution of abdominal, thoracic, and subclavian musculature to respiration and ventilation parameters during three different intensities on a cycle ergometer was assessed pre- and post-intervention. RESULTS: Post-intervention, abdominal, thoracic, and subclavian ventilatory contributions were altered at 2 W·kg-1 (27:23:50 to 31:28:41), 3 W·kg-1 (26:22:52 to 28:31:41), and 4 W·kg-1 (24:24:52 to 27:30:43), whereas minimal changes were observed in the control group. More specifically, a significant (p < 0.05) increase in abdominal contribution was observed at rest and during low intensity work (i.e., 2 and 3 W·kg-1), and a decrease in respiratory rate and increase of tidal volume were observed in the experimental group. CONCLUSIONS: These data highlight an increased reliance on more efficient abdominal and thoracic musculature, and less recruitment of subclavian musculature, in young endurance athletes during exercise following a two-month yoga-based breathing intervention. More efficient ventilatory muscular recruitment may benefit endurance performance by reducing energy demand and thus optimize energy requirements for mechanical work.